2016
DOI: 10.1177/1071100716664364
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Osteomyelitis in Patients Hospitalized With Diabetic Foot Infections

Abstract: Background This study was conducted to evaluate the outcomes of patients with diabetic foot osteomyelitis (DFO) compared to diabetic foot soft tissue infections (STIs). Methods 229 patients who were hospitalized with foot infections were retrospectively reviewed, identifying 155 patients with DFO and 74 patients with STI. Primary outcomes evaluated were the rates of amputations and length of hospital stay. DFO was confirmed by the presence of positive bone culture and/or histopathology. Results Patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 32 publications
0
32
4
1
Order By: Relevance
“…In addition, although the quality of diabetes care in women appears to be higher than in men, the prevalence of DFU in women is higher than in men, which may be due to cultural differences in access to healthcare. Furthermore, in recent studies the duration of diabetes in patients with DFU has been noted as 11-16 years, 19,23,24 but in the Jae-Seung Yun et al 21 study this time has been reported as 6.1 years. This time is important to learn about diabetes and foot care.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, although the quality of diabetes care in women appears to be higher than in men, the prevalence of DFU in women is higher than in men, which may be due to cultural differences in access to healthcare. Furthermore, in recent studies the duration of diabetes in patients with DFU has been noted as 11-16 years, 19,23,24 but in the Jae-Seung Yun et al 21 study this time has been reported as 6.1 years. This time is important to learn about diabetes and foot care.…”
Section: Discussionmentioning
confidence: 94%
“…Various studies have also reported the average age of patients with DFU as between 40-55 years. 19,21,23 There is no significant reason for DFU incidence in middle-age persons but this can be due to the higher prevalence of diabetes in middle-age than in other age groups. In addition, although the quality of diabetes care in women appears to be higher than in men, the prevalence of DFU in women is higher than in men, which may be due to cultural differences in access to healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…The overall amputation rate did not differ significantly between the patients treated for osteomyelitis outside the Charcot region and those treated for osteomyelitis within the Charcot region. Wukich et al [ 28 ] recently reported 16 of 43 patients (37.2%) with CN hospitalized for osteomyelitis underwent major amputation, but this rate can be expected to be lower in less severe cases that can be effectively managed in an outpatient setting such as ours. When considering the level of amputation, the 20% rate of major amputations we reported in cases of osteomyelitis within the Charcot region is comparable to the 23% rate of major amputations reported by Gazis et al [ 29 ] in 47 patients with CN managed by a specialist diabetic foot clinic.…”
Section: Discussionmentioning
confidence: 82%
“…During hospitalization, patients with OM have more surgeries, more amputations, longer hospitalizations, and longer antibiotic exposure than patients with soft tissue infections (STIs), and they are more likely to be readmitted to hospital for an infection. After hospital discharge, up to 48% of patients develop reinfection and require rehospitalization 3,4 . If recurrent OM can be identified early with serum biomarkers, treatments could be initiated earlier and more severe complications such as surgery, amputation, and hospitalization might be avoided.…”
Section: Introductionmentioning
confidence: 99%